American India Pale Ale matrix rich in xanthohumol is potent in suppressing proliferation and elevating apoptosis of human colon cancer cells. (10th May 2014) - Henley, Twila; Reddivari, Lavanya; Broeckling, Corey D.; Bunning, Marisa; Miller, Jeff; Avens, John S.; Stone, Martha; Prenni, Jessica E.; Vanamala, Jairam
Summary American India Pale Ales (IPAs) with and without addition of dark/roasted malts (DRM) and dry hopping (DP) were analysed to determine whether these processes will increase total phenolic content (TP), antioxidant capacity (AA) and the levels of bioactive compounds (xanthohumol, XN and isoxanthohumol, IX). In addition, bioactivity of whole beer matrices, that is, the 'phytochemical team approach, ' was compared to isolated compounds, the 'silver bullet approach, ' by measuring antiproliferative and pro‐apoptotic properties using HCT 116 human colon cancer cells. DP and addition of DRM elevated the XN, IX, TP and AA. Dark malts reduced losses in XN and TP due to filtration. Xanthohumol content positively correlated with phenolic content (r = 0.88, P = 0.0002), indicating that the processes which increased xanthohumol content also elevated other bioactive compounds in beer. However, whole extract from IPAs were more potent in suppressing proliferation and elevating apoptosis in colon cancer cells compared with xanthohumol alone.